Problems of classification and formation land of aviation transport - Novakovska, I.; Skrypnyk, L. (Land Management, Cadastre and Land Monitoring, 2017)
Independent Ukraine had 50 permanently operating airports in 1991. Nowdays there are currently only 20 operating airports in Ukraine, 2/3 of which require reconstruction and substantial technical re-equipment. Without proper investment, Ukraine is able to lose its status as a transit state, as it is unable to recover its transport infrastructure independently. In connection with this, the international experience of the development of airports, particularly in the Baltic States, Georgia, Norway, Poland, deserves special attention. There are the involvement of foreign companies in the management and reconstruction of airports, especially for the development of tourism and recreation, the coordination of the network of airports with the creation of funds for the development of air routes, the implementation of integrated airport development programs, reducing the base of aviation fees due to the growth of non-aviation revenue, increasing competition in the air transport market through the successful functioning of not only national carriers, but also low-cost carriers. The land-resource potential of different types of transport is the basis of development of the transport system of the country, and also the spatial base. Regulation of land use are conducted depend on the main purpose of the land. A feature of aviation land use transport is the concentration on a small area of land of a significant number of objects and structures of various functional purposes, which provide the work of aviation transport, and require appropriate planning of the territories of airfields and airports. Proceeding from the fact that the airfield belongs to strategic objects, and the airport terminal is considered the object of investment, the separation of land of aviation transport by ownership (state, communal, private) and types of use (concession, rent, superficiencies, servitude) are rather complex and extremely important task of land management of the respective territories. Land-use restrictions on aviation transport on adjacent airport territories cover large areas of land. Formation of aviation land-use and ecologically safe use of land of aviation transport is an extremely topical subject of scientific research in modern conditions. The main task is the development of scientific bases and methodological provisions for the formation, operation and regulation of the use of land potential of the aviation industry and methodological recommendations of land management of objects of aviation transport. The indicated problems were almost not investigated by Ukrainian scientists. The separation of land and property of airports of state, communal and private property is the serious problem in modern time. Due to the violation of the principle that an aerodrome is a strategic object that is not able to privatized, and a terminal is an investment object, including private property, only in 5 years it was possible to return the communal property to the Odessa airport, which in 2011 was transferred to offshore investors. The registration of land occupied has not been completed by other airports, and the corresponding legal documents have been issued to them. In accordance with the State Target Program for the Development of Airports, it is planned to implement a range of appropriate measures to ensure the construction, reconstruction and modernization of facilities. It is necessary to reflect in the State Land Cadastre the data on the registration of aerodrome territories as restrictions on land use associated with the operation of aviation transport, to make necessary changes to the Law of Ukraine "On State Land Cadastre" and the Procedure for State Land Cadastre. Key words: transport system, land use regulation, land category, land use regime, restrictions on land use.